Ambulatory colectomy for cancer: Results from a prospective bicentric study of 177 patients. Issue 3 (26th October 2022) - Seux, Héloïse; Gignoux, Benoît; Blanchet, Marie‐Cécile; Frering, Vincent; Fara, Régis; Malbec, Antoine; Darnis, Benjamin; Camerlo, Antoine
Abstract: Background: The implementation of an Enhanced Recovery After Surgery programme after colectomy reduces postoperative morbidity and shortens the length of hospital stay. Objective: To evaluate the short and midterm outcomes of ambulatory colectomy for cancer. Methods: This was a two‐centre, observational study of a database maintained prospectively between 2013 and 2021. Short‐term outcome measures were complications, admissions, unplanned consultations and readmission rates. Midterm outcome measures were the delay between surgery and initiation of adjuvant chemotherapy, length of disease‐free survival and 2‐year disease‐free survival rate. Results: A total of 177 patients were included. The overall morbidity rate was 15% and the mortality rate was 0%. The admission rate was 13% and 11% patients left hospital within 24 h of surgery. The readmission rate was 9% and all readmissions occurred before postoperative Day 4. Eight patients underwent repeat surgery because of anastomotic fistula ( n = 7) or anastomotic ileocolic bleeding ( n = 1). These patients had an uneventful recovery. Sixty‐one patients required adjuvant chemotherapy with a median delay between surgery and chemotherapy initiation of 35 days. Conclusions: Ambulatory colectomy for cancer is feasible and safe. Adjuvant chemotherapy could be initiated before 6 weeks postsurgery. The ambulatory approach may be a step forward to further improve morbidity and oncologic prognosis.